PKM BUDIDAYA IKAN NILA DI LUBANG BEKAS GALIAN TANAH PEMBUATAN BATU BATA DI DESA TANABANGKA KABUPATEN GOWA - Hadijah, Siti; Ibrahim, Bakhtiar (JURNAL PENGABDIAN MASYARAKAT KAUNIAH, 2022)
Squid attractor in the waters has a role as an artificial reef, as a squid collector, and as a squid habitat to lay their eggs. It is therefore, the settlement of the squid attractor in a waters region will create a unique underwater view, which are a layer of squid eggs bed. Additonally, the squid attractor can also to be a nursery habitat and at the end it can be developed to be a potencial fishing ground. The problems are facing by partner groups (group Nelayan Mandiri and group Nelayan Sejahtera Bersama) are: 1) problems in production and 2) problems in business management. For producion problems they result in low production and influence the selling price linearly. Whereas, the poor business management will hamper the production system and will reduce the profit of fishermen group. The purpose of the program of the IbM kelompok nelayan cumi-cumi di Kota Makassar is to provide counseling and demo to the partner groups in order to improve their production and to increase their welfare. The approach methods applied in solving the agreed priority problems of the partners during the realization of the program IbM program is to implemen demonstration system as well as counseling method. There are two selected partner groups, namely Nelayan Mandiri Group and Nelayan Sejahtera Bersama Group. The group selection was based on purposive sampling by the facts that both groups have potential good product and market. From the 5 trips trial on the squid attractor, it was found the total catch of squid was in the range of 10,8 – 11,2 kg on average.